CBT fundamentals : theory and cases - Skinner, Vanessa (Milton Keynes Open University Press, 2014)
This is an indispensable, introductory guide for all mental health practitioners embarking on CBT training. Designed to be read with no prior knowledge of CBT, the book takes the reader through the essential principles and theory of contemporary CBT in a readable and accessible manner. It then outlines the most commonly used models and applies them to a range of mental health problems a novice CBT practitioner will encounter, from depression to anxiety disorders and PTSD. This book makes an excellent use of the case study format and link theory and practice in an instructive and engaging way, promoting your learning. The cases convey a realistic sense of using CBT and working to both engage and promote therapeutic progress in peoples' lives. While placing an emphasis upon promoting engagement and implementing therapeutic interventions with clients and patients, this book also addresses the difficulties, limitations and dilemmas encountered in practice in a pragmatic and constructive manner.
Machine generated contents note: 1.Introduction -- 2.Theoretical background, Including the core concepts of CBT -- 3.The practice of CBT -- 4.Mild to moderate depression -- 5.Low self-esteem, anxiety and depression -- 6.Panic disorder with agoraphobia -- 7.Social anxiety disorder -- 8.Obsessive compulsive disorder -- 9.Obsessive compulsive disorder -- mental compulsions -- 10.Generalised anxiety disorder -- 11.Post-traumatic stress disorder -- single episode trauma -- 12.Perfectionism -- 13.Assertiveness -- 14.Clinical supervision In supporting practice.
Includes bibliographical references and index.
Keywords: Cognitive therapy; Cognitive therapy -- Case studies